2019
DOI: 10.1111/jace.16838
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a SiC‐SiC composite in water vapor environments

Abstract: The article examines degradation of a SiC‐based fiber composite containing Tyranno ZMI fibers in water vapor at elevated temperatures (800°C and 1100°C). Degradation is characterized through mechanical tests under cyclic and quasi‐static tensile loading in the near‐threshold regime, at stresses at or slightly above the matrix cracking limit. These tests are augmented by examinations of fracture surfaces and polished cross‐sections, measurements of fracture mirror radii, and measurements of interfacial debond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Variations in inter-tow mechanical properties as opposed to intra-tow variations were investigated by Zok et al 42 who found no direct correlation between testing fibers close (1 mm) or from a distance (10 mm) to the fracture plane, as well as no evidence of fibers locking (from interphase debris or other fibers) during testing. However, there exists a difference in coating thickness (for both BN and SiC) deposited by CVI proportional to the distance of the tow to the outskirts of the CMC-thus potentially influencing the interfacial measurements.…”
Section: Tow Environment (Inter-tow Variability)mentioning
confidence: 99%
“…Variations in inter-tow mechanical properties as opposed to intra-tow variations were investigated by Zok et al 42 who found no direct correlation between testing fibers close (1 mm) or from a distance (10 mm) to the fracture plane, as well as no evidence of fibers locking (from interphase debris or other fibers) during testing. However, there exists a difference in coating thickness (for both BN and SiC) deposited by CVI proportional to the distance of the tow to the outskirts of the CMC-thus potentially influencing the interfacial measurements.…”
Section: Tow Environment (Inter-tow Variability)mentioning
confidence: 99%
“…For instance, in orthogonal weaves, prismatic matrix pockets with dimensions exceeding 1 mm are common. 34,35 One specific strategy for creating more uniform pore distributions involves use of SiC particles with dimensions comparable to the fiber diameter to fill the larger spaces between the tows and between the layers. The utility of this approach has been demonstrated in oxide composites.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, by considering appropriate chemical kinetics, the above model can be modified to investigate the deleterious effect of water vapor on SiC/SiC composites 46 and to model the harmful effect of moisture in oxide/oxide CMCs 47 . The above model can also be extended to study the effect of environmental barrier coatings on SiC/SiC CMCs 48 …”
Section: Discussionmentioning
confidence: 99%